Pornography, feminist views of - Davis, Berta (The International Encyclopedia of Human Sexuality, 2015)
Feminist women's attitudes toward pornography are significantly polarized. Anti‐porn feminists have taken a position that pornography is degrading toward women, leads to distortion of healthy male‐female sexuality, leads to distorted images of the female body, increases male anxiety about sexual adequacy, sexual compulsivity, and increase violence toward women including rape and sexual harassment.
Disponible en ligne à l'adresse: https://doi-org.proxy.bibliotheques.uqam.ca/10.1002/9781118896877.wbiehs364
Keywords: approches et analyses; cours; discipline; féminisme anti-porn; féminisme pop; pornography; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; thématiques

The mask you live in (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Place: San Francisco, California, USA
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis